Costos de Producción y su Rentabilidad en la Empresa RIO TEXTIL Riobamba-Chimborazo, período 2020-2021. - Urquizo Quisnancela, Daysi Yessenia (2023)
PRODUCTION COSTS AND PROFITABILITY IN RIO TEXTIL RIOBAMBA- CHIMBORAZO COMPANY, PERIOD 2020-2021 The purpose of this research project, titled “Production Costs and Profitability in the Rio Textil Riobamba-Chimborazo Company, Period 2020-2021,” was to analyze raw materials, labor, and indirect manufacturing costs. Textile companies are important for local development, especially those related to the production of clothing and biosecurity accessories. In this context, the aim of this research was to analyze the production costs and profitability of RIO TEXTIL, a company in the city of Riobamba-Chimborazo. The information was collected through surveys, interviews, and observation. The results showed an increase in production costs, which led to a reduction in the company’s profitability. The findings also allowed for sustainable decision-making by improving and changing products. In conclusion, the profitability decreased due to the COVID-19 pandemic, affecting revenue and the increase in raw material prices.